Evaluation of the Antihyperglycaemic Activities, Safety and Phytochemical Profile of Celtis zenkeri Engl - Ayoola, Marcus Durojaye; Odediran, Akintunde Samuel; Famuyiwa, Samson Oluwaseyi; Oluwagbemi, Moyinoluwa; Afolabi, Lateefat Idowu; Oladoja, Farouk Adedeji; Kasumu, Oluwabusayo Emmanuel (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The study evaluated the hyperglycaemia-lowering effects, safety, and phytochemical profile of Celtis zenkeri leaf extract in order to justify its antidiabetic folkloric usage. Methods: Modified OECD test guidelines were used to assess its acute and sub-acute toxicity while its effect on blood parameters such as blood glucose, and haematological and biochemical levels were evaluated using appropriate assays. Both in vitro and in vivo antihyperglycaemic assays were used for the antidiabetic studies while histology of the pancreas, liver, and kidney of the rats was examined after treatment with the extract at 250, 500, and 1000 mg/kg for 21 days. GC-MS analysis was used to determine the chemical constituents of the extract. Results: The results obtained showed that the leaf extract of C. zenkeri was not toxic in rats at 5000 mg/kg. It elicited a significant decrease in the blood glucose levels of the animals but did not affect the haematological and biochemical components of normal rats. It significantly inhibited α-amylase and α-glucosidase actions and gave comparable activity to glibenclamide (5 mg/kg) at all time points at 200 and 400 mg/kg. The extract comparably reduced blood glucose levels with glibenclamide at 100 and 200 mg/kg on days 10 and 14 in drug-induced diabetic rats and maintained the histoarchitecture of the liver, kidney, and pancreas at 250 and 500 mg/kg. Conclusion: The study justified the ethnomedicinal use of C. zenkeri in diabetes management.